PENGEMBANGAN MEDIA SNAKE AND LADDER AUGMENTED REALITY (SLAR) PADA MATA PELAJARAN IPAS TOPIK PERKEMBANGBIAKAN TUMBUHAN DI KELAS IV SEKOLAH DASAR - Hafizah, Siti Sadiah Nur; Andriana, Encep; Syachruroji, A. (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research and development aims to describe the development process, feasibility and students' responses to snake and ladder augmented reality (SLAR) media in the science and sciences subject on the topic of plant reproduction in class IV elementary school. This research uses the Research and Development (R&D) research method with the ADDIE development model. This research uses data collection techniques of observation, interviews, questionnaires and documentation. Data analysis was carried out through descriptive analysis based on Likert and Guttman scales with interpretation referring to Riduwan's criteria. The subjects in this research were 30 class IV students at SDN Serang 3 for the 2024/2025 academic year. Based on the results of the product validation assessment, media expert validation obtained an average score of 86.87% with the criteria